Relativism and universalism in interrogation fairness: a comparative analysis between Europe and China - Vander Beken, Tom (2013)
This paper addresses Chinese interrogation rules from historical and comparative perspectives by relating them to the very different development of interrogation procedure in Europe. A fuller understanding of the evolution of the rules in both contexts is relevant to the present day controversy concerning the universal versus relative nature of interrogation fairness. The comparative analysis reveals that, in fact, the influence of ancient Greek and Chinese civilizations resulted in a great difference between Europe and China regarding legal cultures and institutional arrangements for criminal interrogation procedure. Considering future legal reforms in China, and given the very different historical and institutional context, the likelihood seems low that an ‘autonomous version’ of the right to remain silent and the privilege against self-incrimination will develop on China’s very different soil. However, traditional native resources are also available to legal reformers to ensure a cooperative interviewing style in criminal questioning, and eliminate police-coerced confessions